An Analysis of Service Capacity at Ambon Port - Rosliawati A; Jumriani Jumriani (Institut Teknologi Sepuluh Nopember, 2023)
This research aims to determine container services, to determine projections and the need for container facilities in relation to traffic projections. This study used qualitative descriptive analysis, namely a method that explains in the form of numbers from the growth of activities. This research was conducted with interviews, library research and documentation. The results of the study show that the flow of container ships has increased. In 2020 it was projected to be 355 calls. It will continue to increase until it is projected to be 560 calls in 2029. Meanwhile, the projected realization of the flow of goods in containers in 2020 was 1,243.164 tons, and the realization of containers is predicted to be 2,015,767 tons. The Berth Occupancy Ratio can be maintained at a maximum of 70% according to the standards, so the length of the wharf at Ambon Port where in 2021, the flow of containers has reached 128,662 TEUs with the number of container ships 377 Calls, the length of the container reached 352 meters. As for the storage yard, the required storage area is 42,316 m2. As for the storage yard at Ambon Port, until 2029, the required storage area is 42,316 m2.